QUANTUM LEARNING - Ali, A. Rasyid (Reflective, 2012)
Quantum Learning is the tips, hints, strategies, and the whole process of learning that can sharpen the understanding and memory, as well as making learning as a process that is enjoyable and usefull.Several techniques are proposed techniques improve the ability of self that have been popular and commonly used. However, Bobbi DePorter (1928) developed the techniques that target ultimately aimed at helping students to become responsive and passionate in the face of challenges and realities change.In the early stages of its development, especially quantum learning is intended to help increase successful lives and careers of teenagers in the house, not in intent as methods and strategies to achieve success learning higher in schools. Gradually, the parents of adolescents are also asked to conduct Deporter quantum learning program for them.